Novel phthalimide based analogues: design, synthesis, biological evaluation, and molecular docking studies - Ismail M. M. Othman; Mohamed A. M. Gad-Elkareem; Mohamed El-Naggar; Eman S. Nossier; Abd El-Galil E. Amr (Taylor & Francis Group, 2019)
Pyrazolylphthalimide derivative 4 was synthesized and reacted with different reagents to afford the target compounds imidazopyrazoles 5-7, pyrazolopyrimidines 9, 12, 14 and pyrazolotriazines 16, 17 containing phthalimide moiety. The prepared compounds were established by different spectral data and elemental analyses. Additionally, all synthesized derivatives were screened for their antibacterial activity against four types of Gram + ve and Gram-ve strains, and for antifungal activity against two fungi micro-organisms by well diffusion method. Moreover, the antiproliferative activity was tested for all compounds against human liver (HepG-2) cell line in comparison with the reference vinblastine. Moreover, drug-likeness and toxicity risk parameters of the newly synthesized compounds were calculated using in silico studies. The data from structure-actvity relationship (SAR) analysis suggested that phthalimide derivative bearing 3-aminopyrazolone moiety, 4 illustrated the best antimicrobial and antitumor activities and might be considered as a lead for further optimization. To investigate the mechanism of the antimicrobial and anticancer activities, enzymatic assay and molecular docking studies were carried out on E. coli topoisomerase II DNA gyrase B and VEGFR-2 enzymes.